Assessing the Intention to Use Sports Bracelets Among Chinese University Students: An Extension of Technology Acceptance Model With Sports Motivation - Wang, Yi; Zhang, Xiaotian; Wang, Li (Frontiers in Psychology, 2022)
The use of mobile technology, such as sports bracelets, is gaining popularity as it modifies the ways and processes of learning and teaching in college physical education (PE). However, little empirical evidence can be seen in literature to demonstrate crucial factors that influence university students’ acceptance of sports bracelets. Guided by the technology acceptance model (TAM), this study hence aimed at explaining university students’ intention to use sports bracelets. In total, 445 university students in China responded to a 19-item survey package. Results indicated that users’ attitudes toward technology and perceived usefulness were significant predictors of intention to use sports bracelets. Meanwhile, users’ intrinsic sports motivation significantly promoted users’ positive attitudes toward this technology and was significantly influenced by perceived ease of use and perceived usefulness. Overall, our findings highlighted the importance of stimulating young adults’ intrinsic sports motivation that facilitates their intention to use sports bracelets such that to develop a healthy lifestyle that benefits their physical health.